Asymmetric sensitivity of CEO cash compensation to stock returns: A discussion - Dechow, Patricia M. (Journal of Accounting and Economics, 2006)
Leone, Wu, and Zimmerman [Leone, A., Wu, J., Zimmerman, J., 2005. Asymmetric sensitivity of CEO cash compensation to stock returns. Journal of Accounting and Economics, forthcoming] find that cash compensation (salary and bonus) is more sensitive to price decreases than to price increases. The authors interpret this result as consistent with Boards of Directors exercising discretion to reduce costly ex post settling up in cash compensation. I discuss potential alternative explanations. Specifically, the design of bonus contracts and the placement of the upper bound, and the effect of the Internal Revenue Code Section 162 (m) that limits the deductibility of cash compensation over one million dollars. I also link their results to the managerial power and rent extraction perspective.